THE EFFECT OF DIFFERENT TYPE OF SOLVENT EXTRACTIONON AMINO ACID CONTENT OF SEA CUCUMBER (Holothuria atra) PROTEIN CONCENTRATE - Heriansyah, Ivan; Karnila, Rahman; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract        This study was aimed to determine the effect of different types of solvent extraction on the characteristics of sea cucumber(Holothuria atra)protein concentrates which includes yield, proximate, and total amino acids, and to determine the optimal type of solvent extraction in manufacture of sea cucumber protein concentrates. This research was carried out in 2 stages, namely 1) making of sea cucumber meat flour, 2) making of protein concentrate of sea cucumber meat. The treatment was different type of solvent extraction(ethanol, acetone and methanol). The results of the analysis indicated that the different type of solvent extraction was affected to the characteristics of  sea cucumber protein concentrate, and ethanol solvent was the best solvent in manufacture of sea cucumber protein concentrate with 9.85% of water content (WW), 27.96% of ash content (DW), 0.50% of fat content (DW), 62.04%  of protein content (DW).  Keywords:protein concentrate, solvent extraction, sea cucumber